Descriptive statistics in secondary and higher education: Bibliographical review between 2010 and 2020: Estadística descriptiva en el nivel secundario y superior: revisión bibliográfica entre 2010 y 2020 (Papeles, 2024)
Introduction: The teaching of statistics is often set aside despite being part of the official curricula, leading to a didactic phenomenon that leads to research development in the field and even the need for specific didactics. Methodology: This work presents the results of a bibliographical review and inductive categorization of 70 research articles related to statistical education in secondary and higher levels. The articles were intentionally selected based on the Spanish language and were published in indexed journals and recognized conference proceedings during the period 2010-2020. Results and Discussion: The inductive analysis led to the following categories: Place and year of the research, school level, theoretical framework, focus, problems, objectives, methodology, and most relevant conclusions/results, along with their corresponding subcategories. A part from generating categories and subcategories, this analysis concluded that one of the most frequently explicit research problems is the teaching of statistics without meaning, usually known to prioritize technical knowledge; that the predominant focus is the analysis of students’ knowledge; the most frequent theoretical framework is the Ontosemiotic Approach to Cognition and Mathematical Instruction; and that the most commonly used methodology is questionnaire application. Conclusions: It has come to the conclusion that there is a prevalence given to the “student” as the center of this problem, leading us to reflect on the need to consider (and address) the phenomenon from all its components of the didactic triad: students-teachers-knowledge.
Keywords: Statistics’ didactics; ontosemiotic approach; secondary and higher education; students-teachers-knowledge